Formation of intercultural competence as an urgent need of modern professional activity (Pedagogy of Higher and Secondary Education, 2011)
The thesis is concerned with the problem of intercultural competence formation of marketologiests in the process of globalization. The thesis is concerned with the problem of new innovation technologies in education for competence formation. The theoretical analysis of the research problem form the point of Pedagogy is made. The main approaches to the definition of the term of this method in modern education are defined by the author.
Keywords: problem education; competence; competence formation; modern education main goal